Tradisi Sawur dalam Proses Pemakaman Jenazah Masyarakat Islam Dalam Prespektif Teori Sakral dan Profan Emile Durkheim - M Thoriqul Huda; Adinda Maharani Laila Putri Warma; Nur Maria Setyorini (Universitas Islam Tribakti Lirboyo Kediri, 2023)
Sawur Tradition in the Funeral Process of Islamic Society in the Perspective of Emile Durkheim's Sacred and Profane Theory. The sawur tradition, an essential practice in the funeral process of the Islamic community, has become the center of attention to understanding the complexity of the relationship between local culture and religion. This article analyzes the sawur tradition in the context of Islamic funerals using Emile Durkheim's sacred and profane theory approach. The research method used in this study is field research involving participatory observation and interviews with community members involved in implementing the sawur tradition. This qualitative data was then analyzed through a hermeneutic approach to identify the meaning and significance of the sawur tradition. The sawur tradition involves several symbolic elements, including yellow rice, flowers, and small change, all intended as a form of alms to Allah Swt. The practice also involves various rituals and prayers recited by the bereaved family. Through an analysis based on sacred and profane theories, this article discusses how the sawur tradition reflects the sacred aspects considered sacred in the culture of Islamic societies while still maintaining a balance with the profane aspects of everyday life. The results of this study provide a deep insight into the role of the sawur tradition in maintaining cultural identity and religious values in Islamic societies. Using the analytical method of Emile Durkheim's sacred and profane theory, this article explains the meaning, function, and relevance of this tradition in the context of funerals, as well as illustrating the complex interaction between religion and culture in the daily life of Islamic societies.